Innovative Application Strategies of Light-Emitting Diodes in Protected Horticulture - Xinying Liu; Qiying Sun; Zheng Wang; Jie He; Xin Liu; Yaliang Xu; Qingming Li (Agriculture)
Light-emitting diodes (LEDs) in agricultural systems mainly contribute their capacity to create a precise and constant light spectral environment. However, the potential of LED in crop production was underestimated. LEDs serve not only as efficient artificial light sources for plant growth, but are also a good tool for enhancing biomass production with limited energy consumption. This article reviewed innovative applications of LED in facility agriculture, e.g., plant factory, and greenhouse. Compared to conventional application of LED, innovative lighting strategies such as intermittent lighting, night break, continuous lighting, alternate lighting, dynamic lighting, and end-of-day (EOD) far-red provided by LED light can elevate the production efficiency effectively. However, the scientific explanation of the above lighting strategies remains to be clearly revealed, providing theoretical support for the further optimization of conducting parameters. This review summarizes the physiological effects of different lighting strategies on crop cultivation and illustrates their future application in facility agriculture, aiming to provide novel methods for elevating the energy utilization efficiency and lowering the cost in facility agriculture using artificial light.